138k views
3 votes
HELP PLEASE!!!!!!


<3

HELP PLEASE!!!!!! <3-example-1

1 Answer

5 votes

Answer:

7

Explanation:

Explanation of

f(x) = 2x + 1 for x ≥ 3

f(x) = 3x - 3 for x < 3

when the x in f (x) is greater than or equal to 3 we use the equation 2x + 1

When the x in f (x) is less than 3 we use the equation 3x - 3

we want to find f ( 3 )

because x is greater equal to 3 we use the equation 2x + 1

so to find f ( 3 ) we simply plug in the value of x into the equation

f ( 3 ) = 2(3) + 1

multiply

f ( 3 ) = 6 + 1

add

f ( 3 ) = 7

User Stephen Veiss
by
4.6k points